Evaluasi Implementasi Strategi Bersaing PT. Semen Tonasa dengan Balanced Scorecard - Dwi Catur Yanuari; Muh. Yunus Amar; Nuraeni Kadir (Hasanuddin Journal of Business Strategy, 2019)
A competing strategy allows companies to gain a competitive advantage over their competitors and maintain its success in the market. The study aims to find out the implementation of the strategy of competing on PT Semen Tonasa, as well as to evaluate the implementation of the strategy of competing with 4 Balanced Scorecard indicators, namely a financial perspective, the customer perspective, internal business process perspective, and the learning and growth perspective. This type of research is descriptive qualitative research. Data collection was done using Questionnaires and observation. Data source using primary data and secondary data. The population in this study are all the employees and the customers/consumers of PT Semen Tonasa. In this study using a sample Random Sampling. The analysis of the data used in this study using a Balanced Scorecard approach four perspectives by developing relevant measurement using 12 Critical Succes Factors (CSFs). The results of this research show that the strategy of PT Semen Tonasa already includes the 4 perspectives of a Balanced Scorecard that is Optimizing the improvement of production efficiency, Customer Relationship Marketing, the growth of Sustainable financial performance, Effective Human Resource Management and Sustainability CSR. In line with the strategy of PT Semen Tonasa, PT Semen Tonasa management did some market strategy i.e. strategy, a strategy of production, energy strategy, a strategy of cost efficiency, and HUMAN RESOURCE strategies. The competing strategy implemented by PT Semen Tonasa is leadership strategy cost (Cost Leadership), this is indicated by the majority of the initiatives his strategy focusing on cost efficiency, which aims to suppress the COGS in order to compete with its competitors